A non-functional galanin receptor-2 in a multiple sclerosis patient - Garcia-Rosa, Sheila; Trivella, Daniela Bb; Marques, Vanessa D; Serafim, Rodolfo B; Pereira, José Gc; Lorenzi, Julio Cc; Molfetta, Greice A; Christo, Paulo P; Olival, Guilherme S; Marchitto, Vania Bt; Brum, Doralina G [UNESP]; Sabedot, Thais S; et al. (Springer Nature, 2018)
Multiple Sclerosis (MS) is an inflammatory neurodegenerative disease that affects approximately 2.5 million people globally. Even though the etiology of MS remains unknown, it is accepted that it involves a combination of genetic alterations and environmental factors. Here, after performing whole exome sequencing, we found a MS patient harboring a rare and homozygous single nucleotide variant (SNV; rs61745847) of the G-protein coupled receptor (GPCR) galanin-receptor 2 (GALR2) that alters an important amino acid in the TM6 molecular toggle switch region (W249L). Nuclear magnetic resonance imaging showed that the hypothalamus (an area rich in GALR2) of this patient exhibited an important volumetric reduction leading to an enlarged third ventricle. Ex vivo experiments with patient-derived blood cells (AKT phosphorylation), as well as studies in recombinant cell lines expressing the human GALR2 (calcium mobilization and NFAT mediated gene transcription), showed that galanin (GAL) was unable to stimulate cell signaling in cells expressing the variant GALR2 allele. Live cell confocal microscopy showed that the GALR2 mutant receptor was primarily localized to intracellular endosomes. We conclude that the W249L SNV is likely to abrogate GAL-mediated signaling through GALR2 due to the spontaneous internalization of this receptor in this patient. Although this homozygous SNV was rare in our MS cohort (1:262 cases), our findings raise the potential importance of impaired neuroregenerative pathways in the pathogenesis of MS, warrant future studies into the relevance of the GAL/GALR2 axis in MS and further suggest the activation of GALR2 as a potential therapeutic route for this disease.